Identification of characteristic features of Java programming language for application tool on a lower end mobile phone - Abd. Ridzab, Faizul Azli; Nasrul, Mohammad Ahmad (Universiti Teknologi Malaysia, 2005)
The usage of mobile phone among Malaysian has increased tremendously in the past few years. Looking at the trend of usage, it is beyond doubt that our life will be much dependant on the services and functionalities that it can provide. User of mobile phone has been offered the facilities of downloading new ring tones and games. Games that have been offered here in Malaysia are basically imported from other countries such as the United States and European countries. The applicability of games being offered is much dependant on the capability of mobile phone in use. Most of the games required a high end mobile phone as a platform. There are no tools or applications other than the native mobile phone services such as managing a phone book, watch and calendar available for lower end mobile phone. Even the number of tools available for a high end mobile phone is limited and there is no local developer for this kind of tools or applications in Malaysia. Since the majority of mobile phone owner only uses the ordinary or a lower end mobile phone, a potential user of an application for lower end platform is much greater than the one for a high end. There is a need for a tool on lower end mobile phone in the area where it is suitable to have a tool which are currently available only in Personal Digital Assistant(PDA) and high end mobile phone. The research will basically focusing on the capabilities of Java programming language on a lower end mobile phone and its hardware and software requirements.